PERAN UNTED NATIONS CHILDREN’S FUND (UNICEF) TRHADAP PENGUNGI ANAK-ANAK SURIAN DI YORDANIA (2016-2017) - T. Alfilia Azani; Yusnarida Eka Nizmi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This research explains the role of the United Nations Children’s Fund (UNICEF) in handling refugees, particularly Syirian children in Jordan who were victims of conflict in their native countries. Syirian Children who became victim of the Syirian war had resulted in humanitarian crisis. So to get a sense of security they should evacuate in Jordan. In refugees Kamps, Syirian children are also experiencing critical situations such as poverty, health, lack of basic necessities such as water, and shelter and risk of violence and harassment.This study uses pluralism perspective. Pluralists consider that international organizations are one of the actors who play a role in relations between nations. International organizations theory used in this study to aims to explain about the role of UNICEF, so as to provide explanations of the observed relationships. This study uses qualitative and descriptive analyst methods with the level of analysis of the behavioral group. To analyze this case, the authors collected data from books, journals, websites, reports, and research previous. Researchers also conduct interviews related to the problem to be examined as a primary source of information.This research shows that UNICEF as an international organization focused on fulfilling the basic rights of children has been carrying out its role in responding to the issue of refugee Syirian Children in Jordan. Through its programs, UNICEF has strived to go directly to the field and conduct various cooperation with the government and other non-governmental organizations so that Syirian children in Jordan still get its basic rights. Keywords: Role, UNICEF, Refugees, Conflict, Children